The role of the autonomic nervous system in the etiology of idiopathic scoliosis: prospective electron microscopic and morphometric study - Repko, Martin; Horký, Drahomír; Krbec, Martin; Chaloupka, Richard; Brichtová, Eva; Lauschová, Irena (Child's nervous system, 2008)
OBJECTIVES: The exact etiology of scoliosis is still unknown. The main purpose of this study is to search for the possible causation of scoliosis in the development changes of autonomic nervous structures. In this prospective study, we followed-up the changes in peripheral nerve structures and its discrepancies regarding the concavity and convexity of the scoliotic curve. MATERIALS AND METHODS: We evaluated 12 patients with the idiopathic scoliotic deformity and the control group of 3 patients without any scoliotic deformity. The samples from the peripheral nerves of the convexity and concavity of the scoliotic deformity were drawn during the surgical correction by using the transthoracic approach. The samples were examined by the electron microscopic method and morphometric statistical evaluation. RESULTS: In samples taken from the scoliotic convexity, 23.71% of myelinized nerve fibers (MNF), 12.21% of unmyelinized nerve fibers (UNF), and 5.0% of Schwann cells (SC) were found by the morphometric measurement. There were 17.36% of MNF, 5.82% of UNF, and 5.27% of SC in samples taken from the concavity and 29.9% of MNF, 19.9% of UNF, and 16.7% of SC in the control nonscoliotic samples. Statistically significant differences between both sides of scoliotic deformity (convexity and concavity) and differences between the scoliotic samples and the nonscoliotic control samples were found. In all scoliotic samples, significant morphologic changes were found, mostly in the myelin sheaths and axon fiber abnormalities compression. CONCLUSION: There are significant morphologic changes in spinal autonomic nervous structures in scoliotic patients. These findings can help us in the search for the etiology of scoliosis
Keywords: transmisní elektronová mikroskopie; Humans; Scoliosis; prospektivní studie; Microscopy, Electron, Transmission; Autonomic Nervous System; autonomní nervový systém; lidé; skolióza; Prospective Studies